The Aesthetic Effect of Semantic Translation on English Texts Translated into Arabic (Journal of Misan Researches, 2022)
The past twenty years have witnessed much progress at translation, and good results have been achieved in this field, as it has led to the exchange of knowledge between countries, provided the ground for the exchange of information and experiences, and worked to ensure that countries become a comprehensive and potential driving force for economic growth and human development. Translation has various types, one of these types is the semantic translation where the translator attempts to keep the exact contextual meaning of the original language. This study aims at investigating the extent to which the aesthetic effect (AE) of semantic translation on English texts translated into Arabic namely quotes from George R. R. Martin’ novel "a song of Ice and Fire", Hans Küng's book Islam: "Past, Present and Future" (translated by Al-Shuraiqi and examples translated by Safia Al-Sa'di in the last work of her entitled "Life in Japan". A comparison between the original text aesthetics and the target text (TT) was made based on the selection of sentence structure, lexical and metaphors employed. The data of the study are illustrative examples chosen randomly to be analysed according to Yan Fu’s (2012, cited in Zhang, 2013) triple translation criteria of faithfulness, expressiveness, and elegance in combination with Nida’s (1964) functional equivalence. The results reveal clearly that the chosen translations show a distinct amount of adequacy in terms of expressing the aesthetic effect (AE) in the target text (TT). The results also show that semantic translation appears to be more creatively appropriate in preserving the AE and transferring it into the TT.